A Patient with Microcytic Anemia and Fever. Issue 6 (1st December 2006) - Bhatia, Sacha; Kuriya, Bindee; Stroud, Lynfa; Rachlis, Anita; Adhikari, Neill KJ
Abstract : A 62-year-old man with a history of mechanical aortic valve insertion and ascending aorta replacement in 1997 presented to his family doctor in August 2004 with a two-week history of melena after recently returning from a six-month vacation in Mexico. The patient had no other abdominal complaints. He took warfarin but did not take nonsteroidal anti-inflammatory agents, acetylsalicylic acid or alcohol. The patient had no history of liver or peptic ulcer disease. He had lost 7 kg over the past month, but did not complain of fever or night sweats. On physical examination, vital signs were normal, the second heart sound was mechanical, and there were no abnormal findings. Laboratory investigations showed a borderline microcytic anemia (hemoglobin 76 g/L; mean corpuscular volume 79 fL; mean corpuscular hemoglobin concentration 323 g/L), a therapeutic international normalized ratio (2.6) and an elevated creatinine level (112 µmol/L). His stool was positive for occult blood, although the ferritin level was high (623 µg/L). Other routine blood work was normal. The patient was admitted to hospital for investigation of the anemia.